SEJARAH PERKEMBANGAN GERAKAN TARBIYAH DEWAN DAKWAH ISLAMIYAH INDONESIA DI INDONESIA - Irfan Syuhudi; Suparto (STAI DI AL-HIKMAH, 2024)
The tarbiyah movement is a well-organized action or activity in the field of education with the main objective of educating Muslims by creating various formal and non-formal programs, small or large scope. Indonesia as one of the countries with the largest Muslim population in the world, has many Islamic organizations built by Muslim scholars and scholars who are always competing in developing tarbiyah in Indonesia, one of which is the Indonesian Islamic Da'wah Council (DDII) or also called the Da'wah Council. Dr. Mohammad Natsir as one of the founders of the Da'wah Council in 1967 AD as well as being the first chairman, has always been committed to continuing to foster and educate the ummah not through politics but through da'wah and tarbiyah with its 3 main pillars being mosques, campuses and pesantren. Therefore, the development of Dewan Da'wah's tarbiyah movement is considered important to be discussed in scientific writing. The method of writing this study is qualitative and the theories and information are taken from scientific sources such as books and journals. This study concludes that the role of the Da'wah Council through the Tarbiyah movement in Indonesia is very important because it has built many educational institutions and has given birth to many ulama, da'i, Muslim scholars and national figures who are now felt by many layers of Indonesian society in various regions.